Occupational exposure to styrene and acute health effects among fiberglass-reinforced plastic workers: An integrated environmental and biological monitoring study - Oh-Hyun Kwon; Ki-Youn Kim (PLoS ONE, 2025)
Styrene remains a major hazard in fiberglass-reinforced plastic (FRP) manufacturing. The current 10 ppm 8-h TLV-TWA is half the former limit, and the movement by several European states toward comparable or lower OELs highlights the need for fresh exposure–response data. In this study, eighty-five Korean FRP workers were monitored cross-sectionally. Full-shift breathing-zone styrene was measured by GC-FID; post-shift urine was analysed for mandelic acid (MA) and phenyl-glyoxylic acid (PGA), and dermal uptake was estimated with fluorescent tracers. Neuro-irritative symptoms were assessed by questionnaire and clinically verified in a subset. The results showed that median styrene levels were 18.65 ppm (spray-up), 12.42 ppm (hand lay-up) and 6.37 ppm (closed-mold). Urinary MA and PGA correlated with air levels (r = 0.78, 0.77). Dermal styrene load showed a moderate correlation with urinary MA (r = 0.42, p < 0.001). Symptom prevalence rose from 19% to 71% across exposure quartiles (adjusted OR = 5.6). A biomarker-based model using urinary mandelic acid (MA) with covariates (age, ventilation) showed strong apparent discrimination (AUC = 0.93). We propose 0.38 mg/g creatinine (MA) as a candidate operational (“early-warning”) threshold, pending external validation. In conclusion, integrated air, biological and dermal metrics reveal dose-dependent acute effects at or below 10 ppm. In this cross-sectional analysis, higher styrene exposure was associated with increased acute symptoms at or below ~10 ppm; these associations warrant confirmation in longitudinal studies with repeated biomonitoring. We present 0.38 mg/g creatinine (MA) as a candidate operational (“early-warning”)threshold to flag workers for closer evaluation; external validation is needed, and engineering controls remain the primary means of risk reduction.